First report of characterisation and pathogenicity of bullet wood (Mimusops elengi) sudden decline disease by Ceratocystis in Indonesia - R. PRATAMA; A. Muslim; S. Suwandi; N. Damiri; S. Soleha (Society for Indonesian Biodiversity, 2021)
Ceratocystis manginecans causes wilt and death of plants in several important crops and native vegetation in Indonesia. Ceratocystis wilt was recently found to be causing substantial mortality in bullet wood (Mimusops elengi) in South Sumatra. The aim of this study was to describe the symptomatology of the new disease and characterise isolates of C. manginecans obtained from bullet wood plants. Affected plants showed substantial discoloration of the woody xylem and wilt-type symptoms of the foliage, with the eventual death of the whole plant. Isolations from infected trees yielded a fungus that was similar morphologically to C. manginecans, with typical hat-shaped ascospores and light-coloured perithecial bases. Sequencing of the internal transcribed spacer (ITS) and ?-tubulin of isolates confirmed their identification, grouping them with C. manginecans and separating them from all other Ceratocystis species. This is the first report of C. manginecans in Indonesia causing wilt and death on bullet wood. C. manginecans is an important pathogen, and strategies to reduce losses need to be established in Indonesia because the aggressiveness of C. manginecans to bullet wood has been shown in inoculation experiments